De novo transcriptome sequencing of genome analysis provides insights into Solidago canadensis invasive capability via photosynthesis. Issue 1 (1st January 2019) - Zhang, Yang; Wang, Xiaojuan; Nan, Peng; Li, Jinglong; Gange, Alan C.; Jin, Liang
ABSTRACT: Solidago canadensis is one of the most destructive invasive plants in the East of China, yet nothing is known about its photosynthetic ability at the molecular level. In order to examine the mechanism aiding invasion from the photosynthetic and molecular perspective, transcriptome sequencing and de novo assembly of S. canadensis and its congener S. decurrens (native, non-invasive species) were compared in a bioassay experiment. Results showed that S. canadensis has higher biomass and net photosynthetic rates than those of the native plant, S. decurrens ( P  < 0.05). Based on RNA-seq data, the genes which are closely related to light absorption and electron transfer in S. canadensis were observed to be up-regulated compared with those from S. decurrens, including the process of photosystems I and II, such as PsbP, PsbQ, Psb27, PsbW, PsaG, PetE, and light-harvesting complexes (LHCs). The RT-qPCR verification results of key genes were similar to those from transcriptome. Therefore, our results might partly explain the successful invasion of S. canadensis in China at the level of transcriptome, leading to its enhanced photosynthetic capability.